Complexities of Authentic Assessment Implementation in English Learning at Rural Areas-Based High Schools - Daud, Afrianto; Azhar, Fadly; Isjoni, Isjoni; Chowdhury, Raqib (International Journal of Language Education, 2023)
This research aimed to examine the level of the implementation of authentic assessment by high school English teachers in a rural area of Siak district, Riau Province, Indonesia, and to explore their perception regarding authentic assessment. This research used a mixed method in which both quantitative and qualitative data were collected and analyzed. The research samples were 39 high school English teachers in the Siak region. The research instrument used is a questionnaire comprising 38 closed and three open questions, distributed online via Google Forms. The questionnaire was designed using Likert Scale with options ranging from 1-5 (very poor to very good) Data were also collected using semi-structured interviews to enrich data from the Google Form. This study found that the total average score of quantitative data is 4.1, classified as good. That means the implementation of authentic assessment by English teachers is at a good level. Then from the qualitative data analysis, it appeared that most teachers have a positive perception of authentic assessment as a tool for monitoring and evaluating student learning outcomes. However, there are still some problems faced by the teachers in implementing this assessment, such as the lack of time allotment for the English subject at school and the complexity of the assessment procedures. This implies that some policies are required to make the authentic assessment work well at school levels so teachers can benefit from the assessment for improving English learning at schools.